Changement Climatique et Genre en Agriculture: Plan d’action du Sénégal - MASAE (2025)
Developing countries, including Senegal, face persistent gender inequalities and policy barriers to advance Climate-Smart Agriculture (CSA). The Senegal's Agriculture GCAP examines gender inequalities in agriculture sector in Senegal and outlines action for gender-responsive and inclusive approach in the various sectors of the fight against climate change in Senegal. The action plan is aligned with national policies framework related to gender and climate action